2017
DOI: 10.1007/s11356-017-8686-1
|View full text |Cite
|
Sign up to set email alerts
|

Economic impacts of calving season and parity on reproduction and production traits of buffaloes in the sub-tropics

Abstract: In order to enhance the profitability of dairy buffaloes, it is necessary to develop an understanding of the factors affecting their reproduction and milk production ability. Thus, the objective of this study was to elucidate the economic impacts of calving season and parity on reproduction and production indices of Egyptian dairy buffaloes (1180) reared under subtropical environmental conditions. Buffaloes calving in the autumn season had lesser days open, calving interval, and service per conception (108.25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 13 publications
6
21
0
Order By: Relevance
“…The current study was primarily performed to study the effect of some environmental factors on productive and reproductive traits in the Egyptian buffaloes. The significant effect of calving season on milk yield and reproductive traits were consistent with those reported for Egyptian, Nili-Ravi, and Murrah buffaloes [5,6,20–24]. In the current study, the winter calvers showed the highest TMY and DMY while summer calvers have the lowest ones.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The current study was primarily performed to study the effect of some environmental factors on productive and reproductive traits in the Egyptian buffaloes. The significant effect of calving season on milk yield and reproductive traits were consistent with those reported for Egyptian, Nili-Ravi, and Murrah buffaloes [5,6,20–24]. In the current study, the winter calvers showed the highest TMY and DMY while summer calvers have the lowest ones.…”
Section: Discussionsupporting
confidence: 90%
“…Buffalo’s milk is preferred by the Egyptian consumer due to its white color, acceptable flavor, and good fat percent [18]. The total number of buffaloes in Egypt was estimated to be 4,164,928 heads that produce approximately 2,650,000 ton of milk [6]. Little efforts have been made to improve genetic potentiality for productive and reproductive traits of Egyptian buffaloes.…”
Section: Introductionmentioning
confidence: 99%
“…When labor occurs during the favorable reproductive season, females present a significantly lower postpartum estrus interval when compared to those that have their born outside the reproductive season. During the last 30 days of gestation, the female should be taken to a dry, shaded hygienic picket positioned near the facilities to buffalo observation, parturition and the birth (Hassan, 2017). In the period up to 42 days, the animal is exposed to the pathogenic microorganisms present in the environment, which gradually boost the development of its immune system.…”
Section: Gestation and Puerperiummentioning
confidence: 99%
“…The environmental factors including milking methods, management practices, feeding system, season and geographical area and individual factors such as first-calving age, month of calving, parity and calving interval, calving ease, number of progeny born, significantly affect milk, butterfat and protein yields [1][2][3]. According to Kunaka and Hassan, the fourth parity and those calving in the winter season had the best milk yields [4,5]. Besides, the concentration and yield were influenced by feeding system, milking intervals and automatic milking systems [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%